2013
DOI: 10.5588/ijtld.12.0696
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in tuberculosis patients increases the risk of infection in their contacts

Abstract: Index case smoking increases the risk of LTBI and should be systematically investigated. A reduction in smoking could lower the risk of infection substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…Numerous studies have found individuals with latent TB infection (LTBI) are more likely to be smokers or exposed to second‐hand smoke (SHS) (Table ) . The strength of the associations between LTBI and SHS or direct CS exposure is summarized in Figure a.…”
Section: Tb Infection With Cs Exposurementioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have found individuals with latent TB infection (LTBI) are more likely to be smokers or exposed to second‐hand smoke (SHS) (Table ) . The strength of the associations between LTBI and SHS or direct CS exposure is summarized in Figure a.…”
Section: Tb Infection With Cs Exposurementioning
confidence: 93%
“…Numerous studies have found individuals with latent TB infection (LTBI) are more likely to be smokers or exposed to second-hand smoke (SHS) ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The strength of the associations between LTBI and SHS 15,17,18,21 or direct CS 8,9,11,12,14,16,22,23 exposure is summarized in Figure 1a. There also appears to be an association between the degree of cigarette smoking-as measured by duration or intensity of smoking-and LTBI (Fig.…”
Section: Tb Infection With Cs Exposurementioning
confidence: 99%
“…The effect of smoking on risk of LTBI after adjusting for other risk factors remained strong with an elevated OR of 7·1 (95% CI, 2·8–18). Smoking tobacco increases the risk of acquisition of TB infection [19], development of TB disease [20], and is associated with increased TB mortality [21]. This finding underscores the importance of smoking cessation in this population.…”
Section: Discussionmentioning
confidence: 89%
“…Our estimate of household income may reflect people who were not tax filers but at the same time may underestimate all incomes as per tax laws. Smoking is a well known risk factor for the acquisition of LTBI,17 development of active TB disease18 and death due to TB 19. The prevalence of smoking is high in this population compared with the rest of Canada.…”
Section: Discussionmentioning
confidence: 99%